2009
DOI: 10.1007/s10683-009-9226-8
|View full text |Cite
|
Sign up to set email alerts
|

Are ‘true’ preferences revealed in repeated markets? An experimental demonstration of context-dependent valuations

Abstract: Auctions, Valuations, Economic principles, Anomalies, Experiments, Social interactions, C92, D01, D44,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 21 publications
6
46
0
Order By: Relevance
“…Finally, Tufano (2010) explored the robustness of anchoring for hedonic experiences, rather than goods, by using a binary-choice elicitation procedure. In particular, he examined whether WTA to drink a bad-tasting liquid (similar to the one used by ALP, in a treatment not reported here) was sensitive to an anchor.…”
Section: More Recent Evidencementioning
confidence: 99%
“…Finally, Tufano (2010) explored the robustness of anchoring for hedonic experiences, rather than goods, by using a binary-choice elicitation procedure. In particular, he examined whether WTA to drink a bad-tasting liquid (similar to the one used by ALP, in a treatment not reported here) was sensitive to an anchor.…”
Section: More Recent Evidencementioning
confidence: 99%
“…Tufano (2010) used the anchoring manipulation to increase the variance in subjects' WTA for a bad-tasting liquid, but the manipulation had no effect. Notice that this liquid offers a simple (negative) hedonic experience, like the "annoying sounds" used in Experiment 2 of ALP.…”
mentioning
confidence: 99%
“…WTA bids submitted by subjects asked to consider the $0.50 offer were on average 50% higher than those submitted by subjects asked to consider the $0.10 offer. Building on this experiment, Tufano (2010) also showed that market participants adjusted their bids towards the price observed in previous market periods when, by design, individuals' values should not be affiliated with the market price.…”
Section: The Anchoring Effectmentioning
confidence: 84%